PS01.107: INTERDISCIPLINARY MANAGEMENT OF AORTO-ESOPHAGEAL FISTULA: BETTER SAFE THAN SORRY. (14th September 2018) - Gschwandtner, Elisabeth; Fink-Neuböck, Nicole; Lindenmann, Jörg; Porubsky, Christian; Maier, Alfred; Portugaller, Rupert; Oberwalder, Peter; Deutschmann, Hannes; Dapunt, Otto; Smolle-Jüttner, Freyja-Maria
Abstract: Background: Aorto-esophageal fistula is a rare but life-threatening event evolving spontaneously or—more often—following therapeutic interventions at the esophagus or the aorta. Especially in presence of long-standing inflammation preceding the formation of the fistula, acute surgical closure of the aortic leakage is all but impossible and interdisciplinary treatment is mandatory. Methods: Review of cases of aorto-esophageal fistula within the last 12 years. Results: In our collective of patients undergoing esophagectomy since 2005 (N = 445) we observed 7 cases (1, 5%) of aorto-esophageal fistula. In one case the fistula had developed spontaneously following aspergillosis, one patient had had aortic stenting 29 years before, another one had developed anastomotic dehiscence following intrathoracic esophago-jejunostomy and in 4 cases esophageal stenting had been done. 5 patients presented with slight to dramatic hematemesis which in 2 instances needed endoscopic intervention, 2 had no bleeding. Preoperative angio-CT confirmed aorto-esophageal fistula in 3 cases who underwent aortic stenting prior to the surgical intervention, in 3 patients the fistula was found intraoperatively (aortic replacement N = 1; suture followed by stenting N = 1; operation stopped; aortic stenting, operation the following day). All patients recovered from surgery. In one case inflammation had caused partial necrosis of the aortic wall causing fatal bleeding during operation. Retrospectively, the lesion of the aortic wall could be identified on CT in all but one patient. Conclusion: By interdisciplinary management, involving preoperative stenting or aortic graft implantation in cases not amenable to stenting, patients with aorto-esophageal fistula can be saved and may undergo elective esophageal surgery. Disclosure: All authors have declared no conflicts of interest.